QOL-10. NOVEL MULTIMODAL STUDY OF THREE COGNITIVE REHABILITATION INTERVENTIONS IN LOWER GRADE GLIOMA. (14th November 2022) - Jamora, Christina Weyer; Brie, Melissa; Bracci, Paige; Smith, Ellen; Luks, Tracy; Phan, Stephanie; Braunstein, Steve; Villanueva-Meyer, Javier; Gehring, Karen; Aguilera, Adrian; Bush, Nancy Ann Oberheim; Butowski, Nicholas; et al.
Abstract: BACKGROUND: Grade 2 and 3 glioma survivors (LrGG) are living longer, yet experience cognitive impairments with diminished quality of life (QOL). We present a novel multimodal study of three cognitive rehabilitation interventions in stable LrGG survivors. METHODS: Participants were radiologically stable adult LrGG patients who were off medical treatment for ≥ 6 months with subjective and objective cognitive impairments ( >1SD in 2 or more domains). Patients were offered either In-person cognitive rehabilitation (strategy training including telehealth), or randomized to App-based cognitive rehabilitation (retraining and strategy training) versus Text messaging (strategy training). Intervention duration was 3 months. Neuropsychological testing (with parallel forms) and QOL assessments were conducted at baseline (T1), immediate post intervention (T2), and 6-month follow-up (T3), and analyzed with repeated measures regression or Wilcoxon signed rank tests. RESULTS: Of the 33 analyzed (enrollment ongoing); 15/17 In-person, 5/8 App-based, and 8/8 Texting completed ≥ 80% or greater of interventions. Demographic and clinical characteristics were similar between cohorts. Median age was 48 years (range 27-63), 58% astrocytoma, 30% oligodendroglioma, 15% other (1 pilocytic astrocytoma, 4 diffuse glioma NOS), and 76% had prior radiotherapy. Rehabilitation interventions showed improvements in auditory working memory (T1-T2 In-person p= 0.02, eta 2 = 0.32-medium effect), verbal learning (T1-T3 App-based p= .06, eta 2 = 0.54-large effect; T1-T3 Texting p= .01, eta 2 = 0.75-large effect), and verbal memory (T1-T3 App-based p= .06, rho=0.31-medium effect). CONCLUSION: Significant improvements in cognitive impairments were found with medium to large treatment effects within each cohort. Cognitive rehabilitation via In-person and Texting showed strongest feasibility and acceptability. In-person cognitive rehab showed earlier posttreatment improvements whereas treatment effects for App-based and Texting were noted, but took longer to realize gains. These interventions may show promise for addressing cognitive impairments in LrGG survivors and warrant further investigation.